Model-based multiple rigid object detection and registration in unstructured range data - Breitenreicher, Dirk; Schnörr, Christoph (International journal of computer vision, 2011)
We present a two-stage approach to the simultaneous detection and registration of multiple instances of industrial 3D objects in unstructured noisy range data. The first non-local processing stage takes all data into account and computes in parallel multiple localizations of the object along with rough pose estimates. The second stage computes accurate registrations for all detected object instances individually by using local optimization.
Published online: 26 October 2010
Gesehen am 22.06.2022